Efektivitas Penerapan Zero Waste dalam Meningkatkan Pengetahuan Peduli Lingkungan Anak Usia Dini 5-6 Tahun di TK Negeri Pembina 1 Kota Jambi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to examine the effectiveness of implementing the Zero Waste concept in improving environmental awareness knowledge among children aged 5–6 years at TK Negeri Pembina 1 Kota Jambi. The background of this study is based on the low level of children’s environmental awareness, such as littering, excessive water use, and limited participation in maintaining school cleanliness. The application of the Zero Waste principles, namely reduce, reuse, and recycle, is expected to foster environmentally friendly habits from an early age. This research employed a quantitative approach using a one group pretest-posttest design. The research subjects consisted of 20 children, including 11 boys and 9 girls. Data were collected through observation sheets covering four indicators and eight assessment items related to environmental awareness knowledge. The study was conducted over six meetings, including the pretest, treatment, and posttest stages. The results showed a significant increase in the average score from 16 in the pretest to 28 in the posttest. Statistical analysis indicated a significant effect of the Zero Waste implementation on children’s environmental knowledge (p < 0.05) with a very strong effect size (Cohen’s d = 8.39). Therefore, the Zero Waste approach is effective in enhancing environmental awareness knowledge and can be applied as a contextual, environment-based learning strategy in early childhood education institutions.